Gender, women and primary health care renewal : a discussion paper (WHO GenevaCH, 2010)
Aims to outline the basic elements of gender-equitable primary health care (PHC) reforms. Overviews information on whether and how women and men may be differentially and/or uequally affected by the four primary health care reforms which were suggested by WHO in 2008, viz, universal coverage, service delivery, public policy and leadership reforms. Draws on case examples from different countries to propose measures within the six building blocks of the health system, articulated by WHO in 2007, and larger policy reforms that promote gender equality and health equity and, at the minimum, prevent exacerbation of gender-based health inequities.
References: p.69-76.